ПСИХИЧКИ УТИЦАЈ И КАУЗАЛНОСТ У ОДШТЕТНОМ ПРАВУ - Cvetkovic, Mihajlo (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
Causation is the prerequisite for establishing tort liability and the presumption for damage attribution to a particular defendant. Physical causation is often indisputable but psychological influence is largely problematic because people respond differently to the same stimuli, thus making causal uncertainty inevitable. Induction, incitement, intimidation, persuasion, provocation or seduction are all different, and they need to be valued accordingly. Damage caused by psychological influence is challenging because it sparks a key question: who is to blame – the person who succumbed to influence, or the “influencer” who exerts his psychological impact on another. The issue of causation is here intertwined with other elements of liability, such as culpa and wrongfulness. After providing an overview of Roman law on this matter, the article describes various relations in which the influencer, the tortfeasor and the plaintiff can find themselves regarding mutual psychological stimuli. The major forms and intensity of psychological influence are illustrated by cases from comparative judicial practice. Due to its immaterial nature, psychological influence calls for tailor-made evaluation criteria aimed at determining the legally relevant cause of specific damage (provocation formula). Moreover, the over-extensive concept of psychological influence may lead to unjustified burden for the influencer.